2014
DOI: 10.1105/tpc.114.130484
|View full text |Cite
|
Sign up to set email alerts
|

ABCG26-Mediated Polyketide Trafficking and Hydroxycinnamoyl Spermidines Contribute to Pollen Wall Exine Formation in Arabidopsis  

Abstract: Pollen grains are encased by a multilayered, multifunctional wall. The sporopollenin and pollen coat constituents of the outer pollen wall (exine) are contributed by surrounding sporophytic tapetal cells. Because the biosynthesis and development of the exine occurs in the innermost cell layers of the anther, direct observations of this process are difficult. The objective of this study was to investigate the transport and assembly of exine components from tapetal cells to microspores in the intact anthers of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 60 publications
(90 reference statements)
2
70
0
Order By: Relevance
“…9, M-P), suggesting that OsABCG15 is likely involved mainly in the transport of lipid molecules synthesized in tapetum to microspores for the formation of pollen wall. This assumption can be supported indirectly by the finding that AtABCG26, the OsABCG15 ortholog in Arabidopsis, is involved in exine formation and pollen development (Quilichini et al, 2010(Quilichini et al, , 2014. Furthermore, because of the defective anther cuticle phenotype of osabcg15, OsABCG15 may also function in transporting lipid precursors from the tapetum to anther surface.…”
Section: Osabcg15 Is Mainly Involved In the Transport Of Sporopollenisupporting
confidence: 57%
See 2 more Smart Citations
“…9, M-P), suggesting that OsABCG15 is likely involved mainly in the transport of lipid molecules synthesized in tapetum to microspores for the formation of pollen wall. This assumption can be supported indirectly by the finding that AtABCG26, the OsABCG15 ortholog in Arabidopsis, is involved in exine formation and pollen development (Quilichini et al, 2010(Quilichini et al, , 2014. Furthermore, because of the defective anther cuticle phenotype of osabcg15, OsABCG15 may also function in transporting lipid precursors from the tapetum to anther surface.…”
Section: Osabcg15 Is Mainly Involved In the Transport Of Sporopollenisupporting
confidence: 57%
“…It is generally accepted that sporopollenin, the pollen exine constituent, is produced exclusively in tapetum, and many genes involved in lipid synthesis and exine formation were identified in tapetum (Li et al, 2010;Quilichini et al, 2010Quilichini et al, , 2014Ariizumi and Toriyama, 2011;Chen et al, 2011b;Shi et al, 2011;Zhu et al, 2013;Lou et al, 2014;Yang et al, 2014). However, there is no Figure 11.…”
Section: Anther Cuticle and Pollen Exine Share One Common Aliphatic Smentioning
confidence: 98%
See 1 more Smart Citation
“…1) indicated that the irx9l microspores had similar morphology to wild type at this stage. We also imaged irx9l pollen using two-photon (2P) microscopy, which allows live cell imaging of microspores in intact anthers using the intrinsic autofluorescence of exine under UV excitation (Quilichini et al, 2014b(Quilichini et al, , 2015b. As seen in Figure 1, irx9l microspores appeared to have a thinner pollen wall compared to wild type with less intense emission, but the exine showed similar autofluorescence.…”
Section: Loss-of-function Alleles Of Gts At1g33430 and At1g27600mentioning
confidence: 99%
“…These polyketide sporopollenin precursors are secreted from tapetal cells by the action of the ATP binding cassette transporter ABCG26 (Quilichini et al, 2010(Quilichini et al, , 2014b. Based on the coincidence of probaculae formation and primexine deposition, it is hypothesized that the primexine matrix plays a key role in providing a substrate for anchoring sporopollenin deposition on the microspore surface, and may play a role in exine patterning (Blackmore et al, 2007;Ariizumi and Toriyama, 2011;Quilichini et al, 2014a).…”
mentioning
confidence: 99%